The Effect of News on Bond Prices: Evidence from the United Kingdom, 1900-1920 - Elmendorf, Douglas W.; Hirschfeld, Mary L.; Weil, David N. (The Review of Economics and Statistics, 1996)
We study the relationship of non-quantitative news to bond prices. We select a set of major news events based solely on their significance as judged by historians, and examine the corresponding bond price movements. We find strong evidence that news has some influence on bond price movements, but we find no evidence that news can explain more than a small fraction of those movements.